Models of human resource nutrition and health: exploring the relationships - Beztelesna, Lyudmyla; Pliashko, Olha; Khomych, Sergii; Palamarchuk, Oksana (<center>Conference Proceedings Determinants Of Regional Development</center>, 2021)
The paper examines the relationship between the nutrition models according to the locations (at home and out-of-home) and formats (restaurants, canteens, buffets/cafeterias, etc.), nutrition structure (consumption of basic staples) and health and mortality of the population of Poland and Ukraine. The conducted research allowed determining the importance of these elements in the social and economic development of the countries. The authors identified common and different features in the models of meal arrangements and household eating behaviour. The scholars also analysed the structure and performance of the food business of both countries and clarified its infrastructural and economic features. The research determined that the lack of effective demand in Ukraine does not stimulate food business development of in the catering sector, however, in turn, has long-term consequences for morbidity and mortality of the population. The authors investigated morbidity and mortality from the most common diseases and found that the morbidity rate in Ukraine is higher, and deaths from ischaemic heart disease, also called coronary heart disease (CHD), infectious and parasitic diseases is 6 times higher, whereas mortality from cerebrovascular and circulatory system diseases is 2 times higher than in Poland. The paper found and interpreted dependences between household expenditures on food for different models of meal arrangements, development and health of human resources. The scholars established that household expenditures on eating at home and out-of-home do not have a significant impact on the morbidity of the population in both countries. The performance of public catering companies (their revenue) causes a slight increase in obesity of human resources. Food consumption by human resources and the spread of morbidity in both countries are also poorly linked. However, the study revealed that there are food groups in both countries whose consumption is associated with increased mortality. Such staples as sugar, bread and bakery products were common to both countries. The authors found that food business development via increasing household expenditure on food in the catering sector and increasing the revenue of catering companies contribute to a slight mortality reduction in Ukraine, while in both countries increasing household spending on food prevents increased mortality from malignant neoplasms.